Outcomes and Blood Product Use in 89 Surgically Managed and 79 Medically Managed Cases of Acute Spontaneous Hemoperitoneum in the Dog - Wright, Leah Veronica; Renwick, Michelle; Soh, Rachel W. Y.; Fan, Nicole R.; Tebb, Anna J.; Indrawirawan, Yenny H. (Frontiers in Veterinary Science, 2021)
Objective – To describe a population of dogs with acute spontaneous hemoperitoneum (ASH) that were treated with either surgical or medical management in the first twelve hours after presentation, and to perform a preliminary investigation into whether there were differences in achieving cardiovascular stabilization or patterns of red blood cell (RBC) transfusion between patients treated with early (<12 hours) surgery versus medical management. Design – A retrospective multicentre preliminary study performed on 168 dogs presenting with ASH between January 2015 and May 2019. Patients were excluded if they were euthanized or discharged from hospital within the first 12 hours, or if clinical records were incomplete. All patients received appropriate medical stabilization efforts. Statistical analysis was performed comparing patients that underwent early (<12 hours) surgery and those that did not. Results – 89 patients were in the early surgical group and 79 patients in the medical group. A significantly higher proportion of medical cases were euthanized (p<0.001). A significantly higher proportion of early surgical cases were discharged from hospital (p=0.005). There was no statistically significant difference between groups in achieving cardiovascular stabilization (OR 1.07 p=0.82). A higher proportion of patients with body-weight over 20kg achieved stabilization within 12 hours than those with body-weight of 20kg or less (62.7% vs 41.4%, p<0.01). A higher proportion of patients with splenic conditions achieved stabilization than patients with non-splenic conditions (56.5% vs 28.6%, p=0.05). The odds of receiving an RBC transfusion were higher in the early surgical group than the medical group (OR 3.81 (p <0.001). Conclusions – This preliminary study did not identify a significant difference in the ability to achieve cardiovascular stabilization in the first 12 hours in dogs with ASH that underwent early surgical intervention versus those managed medically. Patients in the early surgical group were more likely to receive a RBC transfusion than those in the medical group. At this time the decision on whether to pursue medical or early surgical management should be made on a case by case basis.